Frequency of Malignancy in Benign enlarge prostate at Peoples Medical College Hospital Nawabshah (Medical Forum Monthly, 2024)
Aim of Study: To determine the frequency of Malignancy in Benign enlarge prostate. Study Design: Prospective observational study: Place and Duration: Two years study from October 2008 to October 2010. Was conducted in Peoples Medical College Nawabshah. Patients and methods: The study comprises 50 patients all were admitted from OPD (Out Patients Department). The patients were evaluated fully after history, clinical examination DRE and specific investigation of PSA X-ray Lumbo sacral spine Trans rectal, Endo luminal ultra sound flow metery Trans rectal biopsy C.T scan and Bone scan and General assessment. All Patients with enlarged prostate included out of 50 patients 48 patients under went surgery and tissue sent for histopathology. Result: In this study of 50 patients of enlarge prostate total number of patients were in age group 55 to 75 years, Out of 50 patients 9 patients suspected malignant on the basis of DRE. But PSA will raise in 7 patients. Regarding the histopathology the results 7 patients showed malignancy adeno carcinoma. Conclusion: Prostate carcinoma more common enlarged prostate as compared to fibro tic prostate.